2017
DOI: 10.1038/s41598-017-13283-6
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis virus infection and age-related cataract

Abstract: This study was performed to investigate the relationships of hepatitis B (HBV) and hepatitis C virus (HCV) infection to age-related cataract, and to assess whether liver damage mediates the hepatitis-cataract association. This study analyzed data in the Korea National Health and Nutrition Examination Survey 2010–2012 on 10,037 participants aged ≥40 years. We performed mediation analysis to address the contribution of serum markers of liver damage, high aspartate (AST, >49.9 IU/L) and alanine aminotransferase (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 31 publications
0
11
0
Order By: Relevance
“…One recent study from Taiwan reported that hepatitis C infection, even without the complication of cirrhosis, is associated with an increased risk of cataract 19. Another study from Korean reported that hepatitis B and hepatitis C infection were significantly associated with cataract 20. The strong association between liver disease and the risk of PACG might increase the risk of cataract in liver disease patients.…”
Section: Discussionmentioning
confidence: 99%
“…One recent study from Taiwan reported that hepatitis C infection, even without the complication of cirrhosis, is associated with an increased risk of cataract 19. Another study from Korean reported that hepatitis B and hepatitis C infection were significantly associated with cataract 20. The strong association between liver disease and the risk of PACG might increase the risk of cataract in liver disease patients.…”
Section: Discussionmentioning
confidence: 99%
“…There are studies where such correlation between hepatitis and cataract has further been augmented by taking in account of chemical markers like Aspartate transaminase (AST) and Alanine aminotransferase (ALT) levels. These studies reveal that raised levels of these enzymes have positive correlation in the development of cataract owing to inflammation 17 .…”
Section: Discussionmentioning
confidence: 83%
“…Recent studies have highlighted an association between hepatitis B (HBV) and hepatitis C (HCV) and cataract 62‐64 . Park and Choi found that infection with HBV and HCV was significantly associated with cataract formation.…”
Section: Cataract and Systemic Diseasementioning
confidence: 99%
“…Recent studies have highlighted an association between hepatitis B (HBV) and hepatitis C (HCV) and cataract. [62][63][64] Park and Choi found that infection with HBV and HCV was significantly associated with cataract formation. Interestingly, the relationship between HBV and cataract was mediated by high ALT and AST enzyme levels, which are markers for significant liver fibrosis and inflammation.…”
Section: Hepatitismentioning
confidence: 99%